2007
DOI: 10.1167/iovs.07-0473
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Corneal Epithelial Innate Immune Response to Pseudomonas Infection by Flagellin Pretreatment

Abstract: Pre-exposure of the ocular surface to TLR agonists may induce protective mechanisms that not only modulate the host inflammatory response but also provide an innate defense against bacterial infection in the cornea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 45 publications
5
58
0
2
Order By: Relevance
“…The bacteriuminduced production of both TNF-␣ and IL-8 was retarded by pretreatment of the cells with flagellin in a concentrationdependent manner; 50 ng/ml flagellin was sufficient to completely block the cytokine secretion induced by both the PAO1 and ATCC 19660 strains of P. aeruginosa (P Ͻ 0.001). Of note, 50 ng/ml flagellin did not induce significant proinflammatory cytokine production in HUCL cells (23). Furthermore, Staph-ylococcus aureus-induced cytokine production was not significantly affected by flagellin pretreatment (data not shown).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…The bacteriuminduced production of both TNF-␣ and IL-8 was retarded by pretreatment of the cells with flagellin in a concentrationdependent manner; 50 ng/ml flagellin was sufficient to completely block the cytokine secretion induced by both the PAO1 and ATCC 19660 strains of P. aeruginosa (P Ͻ 0.001). Of note, 50 ng/ml flagellin did not induce significant proinflammatory cytokine production in HUCL cells (23). Furthermore, Staph-ylococcus aureus-induced cytokine production was not significantly affected by flagellin pretreatment (data not shown).…”
Section: Resultsmentioning
confidence: 85%
“…In a recent study (23), we showed that prolonged activation of TLR5 by flagellin purified from P. aeruginosa PAO1 induced human CECs to become tolerized, as manifested by impaired NF-B activation and greatly decreased production of proinflammatory cytokines in response to PAO1 challenge. To determine whether PAO1 flagellin also induces tolerance to a different strain of P. aeruginosa in human CECs, we pretreated HUCL cells with several doses (10 to 100 ng/ml) of flagellin for 24 h and then challenged them with ATCC 19660, a cytotoxic strain; PAO1 was used as the control.…”
Section: Resultsmentioning
confidence: 95%
“…7 This is partly due to the tight junctions between superficial cells and also partly due to antibacterial peptides and innate immune signalling. [8][9][10][11][12] In addition, bathing tear fluid contains mucins, secretory immunoglobulin A (sIgA), and surfactant protein D, all antimicrobial factors that can bind microbes and potentially alter their interactions with corneal epithelial cells. [13][14][15] Epithelial cells also express several antimicrobial peptides, including human β-defensin 2 (hBD-2), cathelicidin LL-37, 11,12,16,17 and cytokeratin 6A.…”
Section: Corneal Barriers Against Infectionmentioning
confidence: 99%
“…녹농균의 외막에는 숙주의 면역반응유도에 관여하는 PAMP 들이 존재하며, 이중에는 flagella가 포함되어 있다 (Kumar et al, 2007;Raoust et al, 2009). Flagella가 BR 발현에 미치는 효과를 조사하기 위하여 열처리(65℃, 10분)로 사멸시킨 녹농균 △8균 주와 flagella 합성이 저해된 녹농균 fliC mutant (mt) 균주를 pDNNDK이 transfection된 A549에 처리하였다.…”
Section: 녹농균유래 Ndk는 T1ss을 통해 외부로 분비되며 분비된unclassified
“…녹농균은 다양한 세균인자의 분비에 관여하는 분비체계가 잘 발달되어 있는데, 이 중에서 숙주와의 접촉으로 바늘구조를 형성하여 숙주내부로 Exoenzyme S, T, Y 와 같은 활성효소를 주입하는 type III secretion system (T3SS)은 녹농균의 병원성에 중요하게 작용하는 것으로 알려져 있다 (Engel and Balachandran, 2009;Galle et al, 2012). 또한 녹농균의 lipopolysaccharide (LPS)나 flagella는 잘 알려진 pathogen-associated molecular pattern (PAMP)으로서 염증반응 유발에 관여하는 것 으로 알려져 있다 (Kronborg, 1995, Kumar, et al, 2007.…”
unclassified